Evaluasi Kualitas Layanan Perpustakaan Menggunakan Aplikasi SLiMS di SMK Syubbanul Wathon Secang: Evaluation of Library Service Quality Using SLiMS Application at SMK Syubbanul Wathon Secang - Aqmilannaja, Annisa Ulya; Milna Wafirah; Ahmad Fuad Hasyim (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
SMK Syubbanul Wathon Secang Magelang, as a vocational high school education institution based on Islamic boarding schools, adopts the SLiMS (Senayan Library Management System) application to improve the quality of library services that require further evaluation. This study aims to evaluate the quality of library services using the SLiMS application in the SMK Syubbanul Wathon Secang library using the Total Quality Management (TQM) theoretical framework. This study uses a qualitative method with in-depth interviews involving teachers, head of the library, and students, as well as observation and document analysis. Data analysis was carried out using the TQM approach which includes a focus on customers, a system approach, involvement of all staff, continuous improvement, and a fact-based approach. The results of the study indicate that the implementation of SLiMS is not optimal. The main problems found include suboptimal loan circulation, lack of data updates and maintenance, and limited resources. Improving the quality of library services requires improvements so that better services can be provided to all users, including students, teachers, and library managers.